Labor migration of Filipino librarians - Legaspi, Connie Lea C.; Buenrostro-Cabbab, Iyra S.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
This study explores the experiences of OFW librarians by investigating the different push and pull factors that led to their labor migration, examining their perceptions on their current jobs abroad and their place within their organizations through the use of the proposed framework in understanding the experiences of migrant workers. This study utilized an exploratory research design using quantitative and qualitative methods of gathering information. The findings of this study revealed that low quality of life of the family, low income/salary, poverty, lesser opportunity for children’s education and poor services from the government were the primary push factors that drove them out of the Philippines. Alternatively, high income/salary, decent life, equitable compensation, employment potential and better education for the children were the primary pull factors that motivated them to work in their current destination countries. Moreover, it was found that majority of the participants were satisfied with their jobs overseas, specifically in career development, compensation and benefits, belonging and inclusion, work environment and nature of their work. Furthermore, majority of them also demonstrated positive self-perception about their place and value within their current organizations. However, due to the exploratory nature of this study and the small size of the participants, the findings of this study cannot be generalized.
Thesis
Keywords: Filipinos -- Employment -- Foreign countries; Foreign workers, Filipino